2016
DOI: 10.1002/asia.201600803
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Recognition of Amino Acids by Twisted Cucurbit[14]uril

Abstract: Binding interactions between twisted cucurbit[14]uril (tQ[14]) and twenty standard amino acids (AAs) have been investigated by NMR spectroscopy and isothermal titration calorimetry (ITC) in aqueous HCl solutions and in DMSO. The results showed that tQ[14] displays clear binding affinity for AAs with a positively charged side chain or containing an aromatic ring, but weaker binding affinity for AAs with hydrophobic or polar side chains, with the binding mode depending on the type of side chain present in the AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
(73 reference statements)
0
17
0
Order By: Relevance
“…[22,23] Both Bush and Nau found that the larger cavity of cucurbit [8]uril can selectively bind a small organic molecule and an amino acid simultaneously. [24,25] Our research group reported the host-guest binding behavior of twisted cucurbit [14]uril and inverted cucurbit [7]uril with amino acids, [26,27] and for the rst time reported supramolecular complexes of cucurbituril and enantiomeric amino acids. [28] In recent years, studies on the binding behavior between macrocyclic compounds, such as cyclodextrin and crown ethers, and amino acid molecules have been extremely widespread.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[22,23] Both Bush and Nau found that the larger cavity of cucurbit [8]uril can selectively bind a small organic molecule and an amino acid simultaneously. [24,25] Our research group reported the host-guest binding behavior of twisted cucurbit [14]uril and inverted cucurbit [7]uril with amino acids, [26,27] and for the rst time reported supramolecular complexes of cucurbituril and enantiomeric amino acids. [28] In recent years, studies on the binding behavior between macrocyclic compounds, such as cyclodextrin and crown ethers, and amino acid molecules have been extremely widespread.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Cucurbiturils are a series of supramolecular macrocyclic hosts with n glycoluril bridged by 2n methylenes, yielding cucurbituril series (CB [5,6,7,8,10,13,14,15]). CB [5][6][7][8][9][10] (except for CB [13][14][15]) share a common pumpkin-shaped structure with a large hydrophobic cavity and two negatively charged portals.…”
Section: Synthesis Of Cucurbiturilsmentioning
confidence: 99%
“…[5] CB [7] and CB [8] can tune the activities of methylene blue by complexation with dye and hydroxyl radicals in Fenton-mediated oxidation. [9][10][11][12][13] Interestingly, these guests could also be incorporated into the N-termini of proteins, maintaining the binding abilities for CB[n]s. These make it possible to induce protein assembly, leading to tuning the functions subsequently. [7,8] Following the tuning of activities for organic molecules, cucurbituril chemistry has been attractive to tune the properties of proteins owing to the well-defined recognition and binding abilities toward inorganic cations, positive aromatic amino acids (Phe, Tyr and Trp) and peptide motifs in aqueous solutions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Cucurbit[n]uril (Q[n]) [5][6][7] are a class of macrocyclic compounds synthesized by condensing glycoluril and formaldehyde in an acidic medium and are characterized by a rigid hydrophobic cavity and two identical carbonyl-fringed portals. [19,20] Moreover, tQ [14] is not only well soluble in water, but also dissolves in DMSO. Among them, cucurbit [7]uril (Q [7]) is employed as a host molecule due to its good solubility in water and relative large cavity and portals (Figure 1), it can accommodate guest molecules such as drugs, pesticides, dyes, and amino acids.…”
Section: Introductionmentioning
confidence: 99%